1989
DOI: 10.1172/jci114097
|View full text |Cite
|
Sign up to set email alerts
|

Identification and regulation of 1,25-dihydroxyvitamin D3 receptor activity and biosynthesis of 1,25-dihydroxyvitamin D3. Studies in cultured bovine aortic endothelial cells and human dermal capillaries.

Abstract: Because 1,25-dihydroxyvitamin D3 (1,25(OH)2D3) has been shown to play roles in both proliferation and differentiation of novel target cells, the potential expression of 1,25(OH)2D3 receptor (VDR) activity was investigated in cultured bovine aortic endothelial cells (BAEC). Receptor binding assays performed on nuclear extracts of BAEC revealed a single class of specific, high-affinity VDR that displayed a 4.5-fold increase in maximal ligand binding (Nm.x) in rapidly proliferating BAEC compared with confluent, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
193
0
4

Year Published

1991
1991
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 321 publications
(210 citation statements)
references
References 45 publications
11
193
0
4
Order By: Relevance
“…It is also possible that calcitriol mayhaveloweredthe bloodpressure directly. Specific receptors for calcitriol have beenfound in tissues involved in blood pressure regulation in vascularsmoothmuscle (21), althoughit remainsunclear whetherthe binding leads to blood pressure reduction.…”
Section: Discussionmentioning
confidence: 99%
“…It is also possible that calcitriol mayhaveloweredthe bloodpressure directly. Specific receptors for calcitriol have beenfound in tissues involved in blood pressure regulation in vascularsmoothmuscle (21), althoughit remainsunclear whetherthe binding leads to blood pressure reduction.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent evidence suggests that vitamin D receptors are present in tissues, including the vascular endothelium [37], and myocardium [17] and have been shown to decrease proliferation of vascular cell smooth muscle and to improve vasodilation of the endothelium. Additionally, studies have suggested that low concentrations of vitamin D are related to cardiovascular disease, myocardial infarction, stroke, and congestive heart failure [38,39,40].…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…Prospective cohort studies have provided evidence that indicates that low concentrations of total 25(OH)D are associated with an increased risk of CVD (11,12) . The discovery that 1α-hydroxylase is expressed in extra-renal tissues, including the vascular endothelium (13)(14)(15)(16) may help provide a mechanistic basis for an effect of vitamin D status on the processes associated with the development of CVD.…”
Section: Al Found That Black Americans Had Lower Total 25(oh)d Concementioning
confidence: 99%